Movement of the stimulated finger in a Go/NoGo task enhances attention directed to that finger as evidenced by P300 amplitude modulation - Sugawara, Kazuhiro; Akaiwa, Mayu; Matsuda, Yuya; Shibata, Eriko; Saito, Hidekazu; Sasaki, Takeshi (Frontiers in Human Neuroscience, 2023)
Somatosensory cues and the optimal allocation of attentional resources are critical for motor performance, but it is uncertain how movement of a body part modulates directed attention and the processing of somatosensory signals originating from that same body part. The current study measured motor reaction time (RT) and the P300 event-related potential during a required movement response to stimulation of the same body part in a Go/NoGo task under multiple response. In the Movement Condition, participants were instructed to extend their right index finger in response to mild electrical stimulation of the same finger (Go signal) or remain still when receiving electrical stimulation to the fifth right finger (NoGo signal). Movement RTs and P300 amplitudes and latencies were measured under varying Go signal 50% probabilities. In other trial blocks, participants were required to count Go signals but not respond with movement or to ignore all signals while engaged in an unrelated task. Mean RT in the Movement Condition was 234.5 ms. P300 response amplitudes at midline electrodes (Fz, Cz, Pz) were the largest in the Movement Condition. The P300 amplitude at parietal electrode site Pz was significantly greater during Movement Condition trials than during Count Condition trials. The increase in P300 amplitude during trials requiring movement of the same body part receiving somatosensory stimulation suggests that movement itself modulates the attentional resources allocated to that body part.